Microbiomes associated with Coffea arabica and Coffea canephora in four different floristic domains of Brazil - Tomás Gomes Reis Veloso; Marliane de Cássia Soares da Silva; Taís Rizzo Moreira; José Maria Rodrigues da Luz; Aldemar Polonini Moreli; Maria Catarina Megumi Kasuya; Lucas Louzada Pereira (Scientific Reports, 2023)
Abstract Brazilian coffee production relies on the cultivation of Coffea arabica and Coffea canephora. Climate change has been responsible for the decreasing yield of the crops in the country yet the associated microbial community can mitigate these effects by improving plant growth and defense. Although some studies have tried to describe the microorganisms associated with these Coffea species, a study that compares the microbiome on a wider spatial scale is needed for a better understanding of the terroir of each coffee planting region. Therefore, our aim was to evaluate the microbial communities harbored in soils and fruits of these Coffea species in four Brazilian floristic domains (Amazon, Atlantic Forest Caatinga, and Cerrado). One hundred and eight samples (90 of soil and 90 of fruits) were used in the extraction and sequencing of the fungal and bacterial DNA. We detected more than 1000 and 500 bacterial and fungal genera, respectively. Some soil microbial taxa were more closely related to one coffee species than the other species. Bacillus bataviensis tends to occur more in arid soils from the Caatinga, while the fungus Saitozyma sp. was more related to soils cultivated with C. arabica. Thus, the species and the planting region (floristic domain) of coffee affect the microbial composition associated with this crop. This study is the first to report microbial communities associated with coffee produced in four floristic domains that include sites in eight Brazilian states. Data generated by DNA sequencing provides new insights into microbial roles and their potential for the developing more sustainable coffee management, such as the production of biofertilizers and starter culture for fermentation of coffee cherries.